Clinical and pathologic characteristics of appendiceal neuroendocrine neoplasms diagnosed during pregnancy - Twito, Orit; Akirov, Amit; Rosenblum, Rachel Chava; Herzberg, Dana; Oleinikov, Kira; Rotman-Pikielny, Pnina; Grozinsky-Glasberg, Simona (Frontiers in Endocrinology, 2023)
Introduction Although appendicitis occurs in approximately 1:1000 pregnancies, appendiceal neuroendocrine neoplasm (ANEN) diagnosis during pregnancy is very rare. Data on presentation, treatment and prognosis is scarce. Aim To describe ANEN cases diagnosed during pregnancy. Materials and methods A retrospective appraisal of 7 consecutive ANEN patients diagnosed during pregnancy from four Israeli tertiary medical centers and comparison with 17 cases described in the literature from 1965-2021. Results Age at ANEN diagnosis was 26.4 ± 3.5 years (range 21-33). Patients were diagnosed between gestational weeks 6-40, most frequently in the third trimester (53%). The most common presenting symptom was abdominal pain. Tumor size was 14.3 ± 8.9mm (range 3-45mm). In patients from our series appendiceal base involvement was reported in 2/7; mesoappendiceal invasion in 5/7; lympho-vascular invasion in 2/7. Ki67 staining was reported in 6/7 cases and ranged from 1-10%. Pathology details were lacking in most of the previously published cases. All 7 pregnancies in our series resulted in term delivery with no complications, whereas in historical cases there were one first trimester abortion, one ectopic pregnancy, and one stillbirth. Right hemicolectomy was performed in 5/7 patients in our series and reported in 2/17 historical cases. All hemicolectomies were performed after delivery, 3-16 months after appendectomy. Local metastases were reported in two cases. Follow-up duration was 7-98 months for our patients and 3-48 months in 5 historical cases. No disease recurrence, distant metastases or mortality were noted. Conclusions To the best of our knowledge, this is the largest series describing the extremely rare diagnosis of ANEN during pregnancy. Although pathologic characteristics varied, pregnancy outcomes were usually favorable and long-term prognosis was excellent. This data may suggest that a conservative approach to patients with ANEN diagnosis during pregnancy can be considered.